The Optimum Temperature for the Heat Therapy for Meibomian Gland Dysfunction - Borchman, Douglas (Ocul Surf, 2019)
PURPOSE: Numerous devices have been developed to warm the eyelid as a therapy for Meibomian gland dysfunction. The optimum temperature for such therapy was determined. METHODS: Meibum lipid disorder versus temperature was calculated from previously published phase transition parameters measured using infrared spectroscopy. Phase transitions parameters were calculated from meibum obtained from donors with Meibomian gland dysfunction (M(MGD)), donors who were susceptible to dry eye after hematopoietic stem cell transplantations (M(HSCT)) and meibum from donors without dry eye (Mn). RESULTS: Heating Mn to 40 °C increases the lipid disorder by 20.4% to 90 %. Heating the meibum another 4 degrees increases the disorder to 95%. M(MGD) is 73.2 % disordered with no heating. Heating M(MGD) to 41.5 °C increases the disorder by 26.8 % to 90 % disordered. Heating M(MGD) another 5.1 °C increases the disorder to 95%. As meibum from donors who had hematopoietic stem cell transplantations, M(HSCT), is much more ordered, 56.9 % disordered compared with M(n) and M(MGD), a higher temperature above safety limits, 52 and 59 °C is need to disorder M(HSCT) to 90 and 95% disorder. CONCLUSIONS: Heating the eye lid above the phase transition temperature of meibum increases the disorder of meibum lipid which could ameliorate dry eye symptoms. The optimum temperature for disordering Mn and M(MGD) to 90% maximum disorder is 40 and 41.5 °C, respectively. Safety issues and discomfort should be considered in obtaining an optimal level of disorder, especially for severe cases of dry eye.